Inactivation of Escherichia coli ATCC 25922 and Saccharomyces cerevisiae IMR-R-L 962 in grapefruit [Citrus paradisi (Macf.)] juice by UV-C light: changes in bioactive compounds and quality characteristics - la Cava, Enzo Luciano Marcelo (2018)
The viability of UV-C treatment (0.0-2.36 J/cm²) at 254 nm as a non-thermal preservation process for grapefruit juice on microbial inactivation, the organic acids and individual flavonoids, as well as the quality characteristics (pH, ºBrix, titratable acidity, colour, total phenolics and antioxidant capacity) was evaluated. Additionally, pectin methylesterase (PME) activity was also measured. The effects of UV-C on microbial inactivation were assessed by kinetic studies on the inactivation of inoculated grapefruit juice with one strain of Escherichia coli ATCC 25922 and one strain of Saccharomyces cerevisiae IMR-R-L 962. The suitability of Weibull distribution and modified Gompertz models was analysed to characterise the UV-C inactivation kinetics for E. coli and S. cerevisiae in freshly squeezed grapefruit juice. Likewise, the changes after UV-C treatment in citric (CA), malic (MA), ascorbic (AA) and tartaric (TA) acids, as well as naringin (NAR), hesperidin (HES) and neohesperidin (NEO), were quantified by HPLC, whereas the total phenolics and antioxidant capacity (DPPH? and ABTS?+) were quantified by spectrophotometric methods. Nonlinear inactivation curves were successfully fitted with Weibull-type and modified Gompertz models. However, the Gompertz model allowed a better fit and more accurate estimation of the parameters. UV-C treatment at 1.83 J/cm² achieved a 5.18 ± 0.01 and 2.7 ± 0.15 log CFU/mL reduction in E. coli and S. cerevisiae, respectively, whereas no significant changes occurred in CA, MA, TA, NAR, HES, NEO, total phenolics, ABTS?+, pH, ºBrix, titratable acidity and colour of the grapefruit juices (p>0.05). However, PME was partially inhibited and the AA level and DPPH? decreased significantly after treatment, with losses up to 15.9 and 8% (at 1.83 J/cm²), respectively, which were associated with the UV-C dose intensity.